Cognitive Approaches to Morphology: Insights into Mental Lexicon Processing - Isumarni (Indonesian Scientific Publication, 2024)
This narrative review examines cognitive approaches to morphology with a focus on the mental lexicon, exploring how morphological representation and decomposition facilitate word recognition and language processing. The review aimed to synthesize theoretical perspectives and empirical evidence to evaluate the mechanisms that govern morphological awareness and its role in literacy and communication. Literature was collected from multiple databases, including Scopus, Web of Science, PubMed, and Google Scholar, using targeted keywords and Boolean search strategies. Inclusion criteria emphasized studies addressing morphology from cognitive and psycholinguistic perspectives, incorporating experimental, neuroimaging, and review-based methodologies. Findings reveal that morphological families enhance lexical retrieval, while frequency, transparency, and productivity shape access strategies for complex words. Evidence from priming, eye-tracking, and pseudoword experiments confirms the automaticity of morphological decomposition. Bilingual and second-language processing is shown to be shaped by typological similarity, proficiency, and translanguaging practices, resulting in distinct cognitive strategies compared to monolinguals. Neuroimaging studies identify distributed cortical networks, including the left inferior frontal gyrus, supporting morphological processing. Clinical evidence from dyslexia and aphasia underscores morphology’s role in literacy and communication. Systemic and educational factors, including inequities in access and pedagogical design, contribute significantly to observed variability. The review emphasizes the urgency of addressing research gaps in underrepresented languages, age groups, and translanguaging contexts. Pedagogical interventions, such as explicit morpheme-focused instruction, gamified environments, and translanguaging practices, are recommended to strengthen literacy outcomes. Future research should integrate cross-linguistic evidence and neurocognitive approaches to develop inclusive models of morphological processing with broad theoretical and practical implications.